2013
DOI: 10.1016/j.jmb.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Dual Posttranscriptional Regulation via a Cofactor-Responsive mRNA Leader

Abstract: Riboswitches are cis-acting mRNA elements that regulate gene expression in response to ligand binding. Recently, a class of riboswitches was proposed to respond to the molybdenum cofactor (Moco), which serves as a redox center for metabolic enzymes. The 5′ leader of the Escherichia coli moaABCDE transcript exemplifies this candidate riboswitch class. This mRNA encodes enzymes for Moco biosynthesis, and moaA expression is feedback inhibited by Moco. Previous RNA-seq analyses showed that moaA mRNA copurified wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 62 publications
4
55
0
Order By: Relevance
“…In other words, the pgaA terminator could have the properties of a bona fide riboswitch. A precedent for this type of dual regulation was recently set by the demonstration that the molybdenum cofactor-sensing riboswitch of the moaA gene of E. coli includes binding sites for CsrA, which activates moaA expression post-transcriptionally (Patterson-Fortin et al 2013). Other recent findings have linked riboswitch function to Rho activity.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the pgaA terminator could have the properties of a bona fide riboswitch. A precedent for this type of dual regulation was recently set by the demonstration that the molybdenum cofactor-sensing riboswitch of the moaA gene of E. coli includes binding sites for CsrA, which activates moaA expression post-transcriptionally (Patterson-Fortin et al 2013). Other recent findings have linked riboswitch function to Rho activity.…”
Section: Discussionmentioning
confidence: 99%
“…A stochastic RNA folding algorithm predicted that CsrB contains 15 RNA hairpin structures, most of which possess a GGA motif located in a singlestranded loop with conserved flanking sequences, predominantly CAGGA(U/A/C)G (26). Single-stranded GGA sequence motifs also typify the CsrA binding sites of mRNA untranslated leader segments (21,(28)(29)(30)(31)(32)(33)(34)(35). This conserved sequence resembles the Shine-Dalgarno (SD) sequence of ribosome binding sites, to which CsrA often binds in translation repression mechanisms.…”
Section: Csra/rsma: Structure and Functionmentioning
confidence: 99%
“…Studies by Patterson-Fortin et al showed that CsrA binds to the 5= untranslated leader of moaA at two sites within its proposed aptamer domain and activates translation, likely by increasing ribosome accessibility (Fig. 2) (35). These studies introduced a new model for riboswitch function in which two different factors interact with an RNA aptamer to regulate expression.…”
Section: Dynamic Effects Of Csra On Translation Rna Turnover and Trmentioning
confidence: 99%
“…CsrA regulates the expression of genes involved in lifestyle transitions. In Escherichia coli, CsrA activates glycolysis and central carbon pathways (7)(8)(9)(10)(11)(12)(13) and motility (14,15). Conversely, it represses gluconeogenesis (7), glycogen biosynthesis (16)(17)(18)(19)(20), biofilm formation (21)(22)(23)(24), the stringent response (25), and expression of genes involved in other stress resistance and stationary-phase processes, e.g., cstA, hfq, cel, sdiA, and nhaR (24,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%